Generalizing Clustering Inferences with ML Augmentation of Ordinal Survey Data - Kumar, Bhupendera; Kumar, Rajeev (Computer Science, 2024)
In this paper, we attempt to generalize the ability to achieve quality inferences of survey data for a larger population through data augmentation and unification. Data augmentation techniques have proven effective in enhancing models’ performance by expanding the dataset’s size. We employ ML data augmentation, unification, and clustering techniques. First, we augment the limited survey data size using data augmentation technique(s). Next, we carry out data unification, followed by clustering for inferencing. We took two benchmark survey datasets to demonstrate the effectiveness of augmentation and unification. One is on features of students to be entrepreneurs, and the second is breast cancer survey data. We compare the results of the inference obtained from the raw survey data and the newly converted data. The results of this study indicate that the machine learning approach, data augmentation with the unification of data followed by clustering, can be beneficial for generalizing the inferences drawn from the survey data.